Allegiant - Roth, Veronica (New York : Katherine Tegen Books, 2013)
The faction-based society that Tris Prior once believed in is shattered -- fractured by violence and power struggles and scarred by loss and betrayal. So when offered a chance to explore the world past the limits she's known, Tris is ready. Perhaps beyond the fence, she and Tobias will find a simple new life together, free from complicated lies, tangled loyalties, and painful memories. But Tris's new reality is even more alarming than the one she left behind. Old discoveries are quickly rendered meaningless. Explosive new truths change the hearts of those she loves. And once again, Tris must battle to comprehend the complexities of human nature -- and of herself -- while facing impossible choices about courage, allegiance, sacrifice and love.
Keywords: Identity (Philosophical concept) -- Fiction; Science fiction